Behavior And Culture of Novice Voters in Regional Leader Elections - Gita Wibowo, Tifanny Aurelia; Siti Khumayah; Aghnia Dian Lestari (ann4publisher@gmail.com, 2025)
This research aims to explore the behavioral patterns and political culture of novice voters in determining their preferences in the 2024 Regional Leader Election (Pilkada). Novice voters are interesting subject to study because they are an important target for candidates in winning votes. Using qualitative research methods supported by relevant literature and data analysis carried out descriptively using cognitive response theory. This research provides insight into how rationality and social context shape voter behavior. The research results show the enthusiasm of students at SMAN 1 Sindang, Indramayu Regency in participating in the general election. As voters, they show opportunistic political behavior which is characterized by a tendency to change and choose to follow their parents’ choice, and they focus more on practical considerations such as giving money and candidate’s background. However, they will still participate in casting their votes for the candidate they like. In hope is that, the novice voters will become more involved in political activities while managing time for their education and political participation. Keyword: Novice voters, 2024 regional leader elections, cognitive responses, behavior and political culture.